REPRESENTAÇÕES SOCIAIS DE COORDENADORES PEDAGÓGICOS SOBRE SEU PRÓPRIO TRABALHO - Gomes, Selma Veiga Francisco (2011)
This piece of work discusses the Social Representations developed by Pedagogical Coordinators concerning their own jobs. Due to the current tendency for reflections demanded from such professionals, it is presented and mainly considered as a multifaceted professional activity and also one which brings closure to varied and simultaneous tasks. In order to constitute the theoretical-methodological framework which aims at analyzing such subject, reference authors were researched, such as Serge Moscovici (1971), who coined the Social Representation Theory and also António Nóvoa who discusses the Theory of Personhood inscribed within a Theory of Professionalism in order to capture the meaning of a profession. The research was based on the Lei de Diretrizes e Bases da Educação Nacional LDB-9394/96 which is the law that regulates education in Brazil, and also on the Brazilian Classification of Occupations (CBO) from 2002 which outlines and delimits the position and/or the roles of a Pedagogical Coordinator. Regarding the methodology used along the research, it aims at articulating a bibliographically-based research with a field research in which pedagogical coordinators from several educational institutions were interviewed from an open source. The results unfolded new kinds of relations and new ways of understanding the realities of a pedagogical coordinator s job, their professional role, the difficulties faced in their daily professional lives, in order to provide some food for thought concerning the practices and policies related to their roles in the work organization not only demanded from the school but also at the school.